(untitled) (KULT_online, 2024)
Marjorie Mandelstam Balzer’s book Galvanizing Nostalgia? Indigeneity and Sovereignty in Siberia explores the relationship between the ‘prospective’ nature of nostalgic reminiscing and its mobilizing force in construction of indigeneity and strengthening sovereignty of three republics – Sakha (Yakutia), Buryatia, and Tyva (Tuva). The book’s implications remain crucial, even if today’s collective cross-republic activism is difficult to achieve, it is vital to maintaining what remains of their sovereignty.